PORK CRISIS IN ROMANIA IN THE CONDITIONS OF AFRICAN SWINE FEVER IN THE PERIOD 2017-2019 - Agatha POPESCU; Alina MARCUTA; Liviu MARCUTA; Cristina TINDECHE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The paper aimed to analyze the status of pork market during the period 2017-2019 under the impact of African Swine Fever (ASF) in order to assess the consequences on pig livestock, pork production, trade, and price compared to the period 2014-2016. Using the data provided by Faostat and National Institute of Statistics, and the usual methods specific to such an analysis: fixed index, trend line, regression equations and determination coefficient, the obtained results have pointed out that in the interval 2017-2019 versus 2014-2016, of pig livestock, ASF has amplified the decline of pig livestock, slaughtered pigs and their live weight, and pork production. The higher demand than offer on the domestic market increased imports to assure food security and increased pork price. Farmers are discouraged to grow pigs due to the lack of biological material, high price for piglets and feedstuff, high production cost and the high risk that their business to fail, as long as subsidies and aids are missing in pig farming. In consequence, it is needed a new strategy which has to be adapted to the actual situation at the European level destined to counteract the spread of ASF by using efficient measures of traceability and biosecurity along the pork chain. Veterinary authorities have to join their forces to eradicate this disease and produce a vaccine for saving pig livestock. Subsidies and aids are required to sustain pig growing in Romania, where pork is a strategic food.